STUDENTS’ PERCEPTION OF DIGITAL READING TEXTS: A CASE STUDY AT THE ENGLISH EDUCATION DEPARTMENT OF STKIP PGRI BANGKALAN - Suhartini, Suhartini; Ulfa, Siti Maria (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2024)
This study investigated what students' perceptions of reading digital texts and students' preferences for digital text reading. Data was gathered through observation, interviews, and documentation to accomplish this purpose. The interview aims to gather qualitative information about the participants' motivation and interests, the effectiveness of reading digital texts, any difficulties they may have had reading them, and whether they preferred reading print or digital texts. Four students enrolled in five semesters of the English Language Education Department at STKIP PGRI Bangkalan during the academic year 2023/2024 participated in this study. The results showed that the participants had a favorable opinion of reading digital materials because digital texts are more engaging and inspiring, and follow the standard reading format. The main obstacle for students in using digital texts is the less text displayed at once due to the limitations of smartphone screens.